Indigenous communities of Peru: Level of accessibility to health facilities - Hernández-Vásquez, Akram (2022)
“Objectives: This study aimed to geospatially model the level of geographic accessibility to health facilities among Amazonian Indigenous communities in a region of Peru. Methods: Spatial modeling of the physical accessibility of the Indigenous communities to the nearest health facility was performed through cost-distance analysis. The study area was Loreto, the region with the largest territorial area and number of Indigenous communities in Peru. The time required to reach a health facility was determined by cumulatively adding the time needed to cross the grids on the lowest cost route from the Indigenous communities’ locations to the nearest health facility, by considering Amazonian geographical conditions and the main types of transport used. Results: The median time to reach a health facility was 0.96 h (interquartile range: 0.45e2.41). Of the total communities (n ¼ 1043), only 479 (45.93%) communities were within 1 h from the nearest health facility, and 161 (15.44%) were more than 8 h away. The Indigenous communities more than 8 h away from a health estab- lishment were located in the border areas of the depart- ment of Loreto. Conclusion: One in two Indigenous communities is more than 1 h from the nearest health facility.“